2018
DOI: 10.1177/0032885518814704
|View full text |Cite
|
Sign up to set email alerts
|

Participant and Program Characteristics: Correlates of Substance Abuse Treatment Participation and Prison Misconducts

Abstract: Despite the prevalence of substance dependence in incarcerated populations and the correlation between substance use and crime, only 11% receive substance abuse treatment, even as treatment participation may help reduce institutional misbehavior and postrelease recidivism. The current research examined the influence of individual and program factors on substance abuse treatment participation and prison misconducts in a state prison system. Based on analyses of administrative data from 2012 to 2015 and program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This study contributes to research indicating lower misconduct rates are associated with TC's (Auty et al, 2017;Taylor et al, 2019), as well as general research correlating less misbehavior by prisoners in program oriented units (Auty et al, 2017;French & Gendreau, 2006;Randol & Campbell, 2017;Taylor et al, 2019). Findings reported here also provide support for further inquiry into prison units and the impact their functions can have on prisoner behavior.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This study contributes to research indicating lower misconduct rates are associated with TC's (Auty et al, 2017;Taylor et al, 2019), as well as general research correlating less misbehavior by prisoners in program oriented units (Auty et al, 2017;French & Gendreau, 2006;Randol & Campbell, 2017;Taylor et al, 2019). Findings reported here also provide support for further inquiry into prison units and the impact their functions can have on prisoner behavior.…”
Section: Discussionsupporting
confidence: 69%
“… Prendergast et al (2001) and Deitch et al (2004) found lower rates of violent and other infractions between TC participants and general population prisoners in comparisons between TC and non-TC prisons. In a more recent large-scale study, Taylor et al (2019) found lower misconduct rates by TC participants over a 3 year period, and lower misconduct rates over all by prisoners who participated in other programs compared to non-attenders.…”
Section: Prison Units Therapeutic Communities and Misconductmentioning
confidence: 90%
“…A systematic review on the correlates of correctional infractions found that most studies have focused on either individual-level (e.g., age, race, criminal history) or facility-level (e.g., security level, overcrowding, staff-to-inmate ratio) characteristics (Steiner et al, 2014; see also Wooldredge et al, 2001;Wright, 1991). Other studies examine the programs and policies correctional facilities implement to improve behavior and encourage compliance with institutional rules, such as substance use educational and vocational services, treatment and therapy, and visitation (e.g., Lugo et al, 2019;Reidy & Sorensen, 2020;Taylor et al, 2019). However, there have only been a few empirical studies on the effectiveness of security features specifically designed to control and monitor incarcerated individuals' behaviors, even though they have been historically and widely used by correctional agencies.…”
Section: Correctional Safety and Securitymentioning
confidence: 99%
“…A systematic review on the correlates of correctional infractions found that most studies have focused on either individual-level (e.g., age, race, criminal history) or facility-level (e.g., security level, overcrowding, staff-to-inmate ratio) characteristics (Steiner et al, 2014; see also Wooldredge et al, 2001; Wright, 1991). Other studies examine the programs and policies correctional facilities implement to improve behavior and encourage compliance with institutional rules, such as substance use educational and vocational services, treatment and therapy, and visitation (e.g., Lugo et al, 2019; Reidy & Sorensen, 2020; Taylor et al, 2019).…”
Section: Correctional Safety and Securitymentioning
confidence: 99%